A soft body as a reservoir: case studies in a dynamic model of octopus-inspired soft robotic arm - Nakajima, Kohei; Hauser, Helmut; Kang, Rongjie; Guglielmino, Emanuele; Caldwell, Darwin G.; Pfeifer, Rolf (Frontiers in Computational Neuroscience, 2013)
The behaviors of the animals or embodied agents are characterized by the dynamic coupling between the brain, the body, and the environment. This implies that control, which is conventionally thought to be handled by the brain or a controller, can partially be outsourced to the physical body and the interaction with the environment. This idea has been demonstrated in a number of recently constructed robots, in particular from the ﬁeld of “soft robotics”. Soft robots are made of a soft material introducing high-dimensionality, nonlinearity, and elasticity, which often makes the robots difﬁcult to control. Biological systems such as the octopus are mastering their complex bodies in highly sophisticated manners by capitalizing on their body dynamics. We will demonstrate that the structure of the octopus arm cannot only be exploited for generating behavior but also, in a sense, as a computational resource. By using a soft robotic arm inspired by the octopus we show in a number of experiments how control is partially incorporated into the physical arm’s dynamics and how the arm’s dynamics can be exploited to approximate nonlinear dynamical systems and embed nonlinear limit cycles. Future application scenarios as well as the implications of the results for the octopus biology are also discussed.